Cervical origin of left subclavian artery: A rare anomaly - Ponnusamy Shunmuga Sundaram; Kiron Sukulal; Sasidharan Bijulal; Jaganmohan A Tharakan (Wolters Kluwer Medknow Publications, 2014)
A 22-year-old lady was referred to our institute for the management of pulmonary atresia with hypoplastic pulmonary arteries. Computed tomographic Angiography (CTA) showed right aortic arch with left brachicephalic artery as the first branch, which trifurcated into internal carotid, external carotid and subclavian artery high up in the neck at the level of third cervical vertebra. The left subclavian artery then travelled back caudally and entered into the arm after giving rise to a large collateral artery. This is the first ever-reported case of cervical origin of left subclavian artery (COLSA) in the literature. This anomaly can be explained by the absence of left fourth aortic arch with left subclavian artery arising from the left third aortic arch.